2007
DOI: 10.1103/physreva.76.043413
|View full text |Cite
|
Sign up to set email alerts
|

Rotational-state-selective field ionization of molecular Rydberg states

Abstract: This paper presents state-selective field ionization spectra of highly excited Rydberg states of NO. The competition between electron-nuclear coupling and electron-field coupling is investigated and it is shown that the slew rate of the electric field can be exploited to control the rotational quantum state composition of field-ionized molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Similar fields were used to ionize neutral Rydberg molecules for detection immediately after photoexcitation. To detect molecules in long-lived Rydberg states, slowly-rising pulsed ionization fields 31,59 (rise time ∼ 2 µs) were applied 126 µs after laser photoexcitation. In these measurements the electric field amplitude at the time of ionization was correlated with the electron signal detected at MCP2 to provide information on the internal quantum state populations.…”
Section: Electric Field Ionizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar fields were used to ionize neutral Rydberg molecules for detection immediately after photoexcitation. To detect molecules in long-lived Rydberg states, slowly-rising pulsed ionization fields 31,59 (rise time ∼ 2 µs) were applied 126 µs after laser photoexcitation. In these measurements the electric field amplitude at the time of ionization was correlated with the electron signal detected at MCP2 to provide information on the internal quantum state populations.…”
Section: Electric Field Ionizationmentioning
confidence: 99%
“…High Rydberg states of NO have been the subject of numerous experimental and theoretical investigations (see, for example, Refs. 6,[20][21][22][23][24][25][26][27][28][29][30][31][32]. The work reported here builds on these detailed studies of the structure and dynamics of Rydberg states of NO, many of which were carried out in particular in the context of the development of ZEKE photoelectron spectroscopy, 6 and more recent studies of plasma formation in cold Rydberg gases.…”
Section: Introductionmentioning
confidence: 99%
“…For low density Rydberg gases, SFI has served as an exacting probe of the coupling of electron orbital angular momentum with core rotation. Studies of nitric oxide in particular have shown that nf (2) Rydberg states of NO traverse the Stark manifold to form NO + in rotational states N + = 2 and 0 [47]. These experiments operate in a diabatic regime, employing a slew rate of 0.7 V cm −1 ns −1 .…”
Section: Experimental Backgroundmentioning
confidence: 99%
“…Many previous studies have recognized that the rate of predissociation, which depends sensitively on Rydberg orbital angular momentum, , limits transitions readily detected by ionization from A 2 Σ + N = 0 to those in the N = 1 nf Rydberg series that converges to the NO + rotational level, N + = 2 [61][62][63][64]68]. This hydrogenic series, n 0 f (2), defines a particular subset of nitric oxide Rydberg gas initial states that evolve to form a durable ultracold plasma.…”
Section: Discussionmentioning
confidence: 99%